Government Debts and Financial Markets in Europe. - Caselli, Fausto Piola (Financial HIST., 2015)
Contains essays by historians of economic and financial history. It illuminates the relationships between government indebtedness and the development of financial markets in Europe from the late Middle Ages to the late twentieth century.